PRICING METHOD: THE MAIN METHODS AND MECHANISMS OF PRICE FORMATION AND CALCULATION, EXAMPLES, CHARACTERISTICS - Kazakov Firdavs Farxod ugli (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
in a free market, it is very important to correctly determine the value of a product or service, which in most cases is not regulated at the legislative level. The efficiency of trade and, as a result, the economic feasibility of the enterprise directly depends on this parameter.